Progress in the discovery of new bioactive substances from deep-sea associated fungi during 2020-2022 - Wang, Zimin; Qader, Mallique; Wang, Yufei; Kong, Fandong; Wang, Qi; Wang, Cong (Frontiers in Marine Science, 2023)
The marine environment can harbor millions of macro-and micro-organisms. These habitats gained more attention as they produced a plethora of novel secondary metabolites. Recently marine-derived fungi become the hotspot in drug discovery and development. Deep-sea-associated fungi are an important group of marine fungi living in the ocean below 1000 m. The extreme living environment of high pressure and low temperature made the deep-sea-associated fungi difficult to collect and also resulted in the evolution of the special secondary metabolic genes in them. Although the vast majority of deep-sea fungi undiscovered and very fewer natural products have been reported from them compared to the fungi derived from the near and shallow sea, they are still considered to be potential prolific sources of novel bioactive compounds that are of considerable interest for new drug leads. This review will expound on the sources of strains, chemical structures, and biological activity of 184 new natural products isolated from 46 deep-sea-associated fungi, which were reported from 2020-2022.